2011
DOI: 10.1016/j.bpj.2011.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cytoskeleton and Tether Extraction

Abstract: We perform a detailed investigation of the force × deformation curve in tether extraction from 3T3 cells by optical tweezers. Contrary to conventional wisdom about tethers extracted from cells, we find that actin filaments are present within them, so that a revised theory of tether pulling from cells is called for. We also measure steady and maximum tether force values significantly higher than previously published ones for 3T3 cells. Possible explanations for these differences are investigated. Further experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
103
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 35 publications
23
103
1
Order By: Relevance
“…In biological applications, transparent microspheres are usually employed as force transducers, with laser light of wavelength λ ∼ 1 μm to avoid damage to living cells. An example is the measurement of membrane elastic properties by pulling tethers (nanotubes) from the cell surface [5]. The cell rests on a glass slide that forms the bottom of the sample chamber containing the water that the cell is immersed in.…”
Section: Introductionmentioning
confidence: 99%
“…In biological applications, transparent microspheres are usually employed as force transducers, with laser light of wavelength λ ∼ 1 μm to avoid damage to living cells. An example is the measurement of membrane elastic properties by pulling tethers (nanotubes) from the cell surface [5]. The cell rests on a glass slide that forms the bottom of the sample chamber containing the water that the cell is immersed in.…”
Section: Introductionmentioning
confidence: 99%
“…We find the ratio is smaller at 1-1.5 which suggests that if E. 16 of Pontes et al is valid, the contact patch area is two to three-fold greater than nanotube radius, i.e., for nanotube radius of 50 -100 nm 34,74,77 the patch radius is predicted to be 100 -300 nm. We do find as shown for many different cell lines 34,75 that membrane nanotubes formed from HN-31 cells contain F-actin ( Figure 9B). The samples were fixed < 1 minute after the onset of the tensile load ( Figure 1) and this represent a time scale comparable to our force experiments.…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the mentioning
confidence: 60%
“…We find the median (mean) and standard deviation of the force to form a single nanotube for the overshoots and nonovershoots is 54 (62) ± 15 (8) Koster et al 76 showed for membrane vesicles that the force barrier for the formation of a membrane nanotube increased linearly with the area the force is exerted on. Pontes et al 34 demonstrated this with NIH3T3 fibroblasts by showing the ratio ≡ 5.6 was dependent on the ratio between radius of formed nanotube and radius of contact area between bead and cell (coined the patch radius). We find the ratio is smaller at 1-1.5 which suggests that if E. 16 of Pontes et al is valid, the contact patch area is two to three-fold greater than nanotube radius, i.e., for nanotube radius of 50 -100 nm 34,74,77 the patch radius is predicted to be 100 -300 nm.…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the mentioning
confidence: 92%
See 2 more Smart Citations